STUDI TENTANG TENUN SONGKET NAGARI TANJUANG SUNGAYANG DI BATUSANGKAR - Diki Asla Putra; Budiwirman .; Zubaidah . (Serupa The Journal of Art Education, 2012)
Abstract Songket is a kind of weave fabric handicraft. It is made from yarn, cotton, silk and others. The technique to make it is by putting the weft horizontally to the loom, the row of vertical yarns. The quality of songket usually value from material quality, the arranging of color, the theme and pattern of decorated and the variety of tema.The design of this research is qualitative research that using descriptive method. The data that had been collected are include words, picture and not nominal. This research is held by interviews method, observation and documentation through photography.Based on the finding from the research it can be concluded that songket weaving from balapaktanjuangsungayanghave many differences from other weaving fabrics, especially in tema, color, work technic and the material.   Kata Kunci : Songket, Tanjung Sungayang